2014
DOI: 10.1007/s00414-014-1025-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Y haplogroups and autosomal AIMs reveals intra-population substructure in Bolivian populations

Abstract: For the correct evaluation of the weight of genetic evidence in a forensic context, databases must reflect the structure of the population, with all possible groups being represented. Countries with a recent history of admixture between strongly differentiated populations are usually highly heterogeneous and sub-structured. Bolivia is one of these countries, with a high diversity of ethnic groups and different levels of admixture (among Native Americans, Europeans and Africans) across the territory. For a bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…In admixed populations, it is essential to analyze matri and patrilineage as well as bi‐parentally transmitted markers of the genome because both can reveal different geographic ancestry components [Kayser et al, , ]. In the results presented herein, the genetic ancestry backgrounds of the Argentines and Bolivians analyzed in this study were similar to those previously described; for the reason that the European ancestry component prevailed in metropolitan Argentina whereas the Native American component was the most prevalent in the North‐western region and Bolivia [Corach et al, ; Avena et al, ; Vullo et al, ] (Supplementary Fig. S2).…”
Section: Discussionsupporting
confidence: 80%
“…In admixed populations, it is essential to analyze matri and patrilineage as well as bi‐parentally transmitted markers of the genome because both can reveal different geographic ancestry components [Kayser et al, , ]. In the results presented herein, the genetic ancestry backgrounds of the Argentines and Bolivians analyzed in this study were similar to those previously described; for the reason that the European ancestry component prevailed in metropolitan Argentina whereas the Native American component was the most prevalent in the North‐western region and Bolivia [Corach et al, ; Avena et al, ; Vullo et al, ] (Supplementary Fig. S2).…”
Section: Discussionsupporting
confidence: 80%
“…Using data from the 46 AIM-Indels, pairwise F ST genetic distances were calculated between the five Patagonian populations from this study, and samples from six Argentinian provinces [15], six South American populations from Brazil [23], Bolivia [24] and Colombia [25,26], as well as the European, African and Native American HGDP-CEPH reference populations [22] (S5 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Dye-labeled amplified fragments were separated and detected using an ABI3130 Genetic Analyzer (Life Technologies), and automated allele calls were obtained with GeneMapper v.3.2 (Life Technologies). This panel showed to be highly informative to analyze genetic admixture in different Latin-American populations, including Argentina [15], Brazil [23], Bolivia [24] and Colombia [25,26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, urban towns of Argentina, Mexico, Chile, Colombia, Uruguay, and South of Brazil showed that >55% of the global ancestry belongs to European contribution followed by Native American and <10% of African contribution 55,60,61. Instead, rural Mexico and urban populations in Peru and Bolivia showed the major contribution of Native American ancestry in part due to the high population density of aboriginal in the region at the moment of the conquest 6063…”
Section: Genetic Ancestry Influences Hcv Pharmacogenomics In Latin Ammentioning
confidence: 99%